APA Educator Portfolio Analysis Tool - Latha Chandran; Maryellen Gusic; Constance Baldwin; Teri Turner; Elisa Zenni; J Lindsey Lane; Dorene Balmer; Miriam Bar-on; Daniel Rauch; Diane Indyk (Association of American Medical Colleges, 2009)
Abstract This resource is a tool for the evaluation of educator portfolios, based on measurable outcomes designed to allow reproducible analysis of the quality and impact of educational activities. The analysis tool is organized in tabular format and combines 18 quantitative, 25 qualitative, and five holistic ratings. We sought a balance between qualitative and quantitative items in a tool that captured important nuances of educational performance but was not too long to preclude practical use by a promotions committee. A unique feature of this tool is the inclusion of seven index scores that combine several quantitative measures to measure depth and impact of an educational activity. For example, the curriculum impact index, which measures the impact of all the curricula developed by a faculty member, combines for each curriculum the number of learners taught, a geographic impact score, and an implementation score. Qualitative items are scored on a 3-point rating scale; verbal specifications for an intermediate rating are provided. The accompanying instructions for use provide step-by-step guidance on how to score both quantitative and qualitative items with specific examples. Use of this comprehensive-yet-practical tool is offered as a method to enhance opportunities for the promotion and advancement of educators, based on well-defined and documented educational outcome measures. It is relevant for clinical educators across disciplines and across institutions. Our lessons learned as a consensus development team may prove useful to other raters who use or adapt this tool. Evaluation of quantitative items taught us repeatedly to keep it simple. Proliferation of items is tempting, but a focused selection of essential items makes the tool practical. Evaluation of qualitative items needs to be grounded in sound principles that are clear to the rater. Specification of ratings for each item was critical to achieve concordance in our qualitative ratings.